Biodiversity and National Accounting - Hamilton, Kirk (World Bank, Washington, DC, 2013)
Biodiversity, a property of natural areas, provides a range of benefits to the economy including bioprospecting rents, knowledge and insurance, ecotourism fees, and ecosystem services. Many of these values can be broken out in the System of National Accounts, leading to better estimates of the economic losses when natural areas are degraded or destroyed. Developing countries harbor the great majority of biodiversity, and this diversity provides benefits, including knowledge and carbon sequestration, to the whole world. However, protecting biodiversity is particularly costly for developing countries: the opportunity cost of foregoing development of natural areas exceeds 1 percent of gross domestic product in 58 developing countries, versus only four OECD countries. The Global Environment Facility can offset these costs through grant finance, but annual Global Environment Facility finance and co-finance averages only 8 percent of the opportunity costs faced by low-income countries.